Students follow up on social networking sites to gratifications achieved A field study of a sample of students of the College of Mass (Communication - University of Baghdad) - M. Mohammed Kadhim Majeed (Genius Journals, 2022)
This research is descriptive research in its kind, and it uses the survey method in the context of what is related to the survey of the targetaudience in the research, in order to identify the extent of the impact of social networking sites on university students in their exposure to daily events in Iraq and in order to come up with specific scientific conclusions that answer the questions. Research questions. The importance of the research lies in the extent of the spread of the use of social media, which has become an integral part of the lives of societies. In fact, individuals have become accepting to use these sites to a degree that may reach addiction at times, in addition to that these sites attract many age groups in different societies, especially the category of University youth.The research required dividing it into three sections. The first topic dealt with the methodological framework of the research, which included the research problem, its importance, objectives and methodology, as well as the research community, its sample and its fields. For research, which included the presentation and interpretation of the results of the analysis.
Keywords: results; sites; objectives; problem